Antioxidant Level and Sensory of Dragon Fruit (Hylocereus undatus) Peel Tea Infusion Made by Partially Fermented Process - Anjar Ruspita Sari; Ratih Hardiyanti (Agroindustrial Journal, 2017)
Dragon fruits are usually consumed by people directly or being processed into juice. Therefore,the major by-product of dragon fruits is the peel. As by-product, dragon fruit peels have higherantioxidant level than pulp especially for White Dragon Fruits (Hylocereus undatus). Thisresearch is carried out in order to evaluate the antioxidant level and sensory of dragon fruitpeel tea which produced through a partially fermented process. The objective of this researchis to investigate the effect of withering time and rolling time on antioxidant level and sensory ofdragon fruit peel tea. Withering time varied in 30, 60, and 120 min while the rolling timevaried in 10, 20, and 30 sec. 2, 2, diphenyl-1-picrylhydrazil (DPPH) assay showed that radicalscavenging activities of dragon fruit peel tea infusion increased with the longer withering timeand shorter rolling time. Likewise the total phenol content (TPC) assay demonstrated theamount of phenol increased with the longer withering time and shorter rolling time. Therewere found that the dragon fruit peel had 29.58% in proportion compared with the whole fruitand vitamin C content in the peel higher than that in the pulp. The longer withering time andshorter rolling time will increase the phenol total content, antioxidant activity, and thelightness color, but decrease the acidity degree of tea infusions. In addition, the withering timewas 120 min and rolling time was 10 sec had higher Antioxidant activity 41.19% and the totalphenol 55.93 mg/L.